2017
DOI: 10.1016/j.envpol.2017.06.034
|View full text |Cite|
|
Sign up to set email alerts
|

C1-C2 alkyl aminiums in urban aerosols: Insights from ambient and fuel combustion emission measurements in the Yangtze River Delta region of China

Abstract: We measured low molar-mass alkyl aminiums (methylaminium, dimethylaminium, ethylaminium and diethylaminium) in urban aerosols in the Yangtze River Delta region of eastern China in August 2014 and from November 2015 to May 2016. After examining artifact formation on sample filters, methylaminium, dimethylaminium and ethylaminium concentrations were quantified. The three C1-C2 aminiums exhibited a unimodal size distribution that maximized between 0.56 and 1.0 μm. Their concentrations in PM were 5.7 ± 3.2 ng m, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 78 publications
5
20
0
Order By: Relevance
“…Previous studies reported contradictory conclusions on the relationship between amines and O 3 . For example, in Shen et al (2017), MA and DMA, were found to be positively correlated with O 3 in urban Nanjing, consistent with the present study, but Zhou et al (2019) found a negative correlation between amines and O 3 in urban Shanghai in summer of 2013, and no correlations were found in other seasons. Generally, amines in gaseous phase could be oxidized by oxidants such as O 3 and OH radical (Ge et al, 2011a;Nielsen et al, 2012;Tong et al, 2020), while the amines in particle phase might fail to show a negative correlation with O 3 .…”
Section: Level Of Pollutantssupporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies reported contradictory conclusions on the relationship between amines and O 3 . For example, in Shen et al (2017), MA and DMA, were found to be positively correlated with O 3 in urban Nanjing, consistent with the present study, but Zhou et al (2019) found a negative correlation between amines and O 3 in urban Shanghai in summer of 2013, and no correlations were found in other seasons. Generally, amines in gaseous phase could be oxidized by oxidants such as O 3 and OH radical (Ge et al, 2011a;Nielsen et al, 2012;Tong et al, 2020), while the amines in particle phase might fail to show a negative correlation with O 3 .…”
Section: Level Of Pollutantssupporting
confidence: 91%
“…Amines were also found to be correlated with secondary inorganic components including , , and and K + , as well as levoglucosan, which is a key tracer of a biomass burning plume (Pachon et al, 2013), indicating that anthropogenic activities such as biomass burning were the possible sources of amines in the study site (Zheng et al, 2015). Amines were also positively correlated with the trace gas pollutants such as SO 2 , NH 3 , HNO 3 , HCl, and HONO, consistent with the strong correlation between amines and SO 2 that was previously reported (Shen et al, 2017). Interestingly, MA, DMA, and DEA positively correlated with O 3 , which was considered to be a species with oxidizing capacity (Ge et al, 2011a).…”
Section: Level Of Pollutantssupporting
confidence: 88%
See 1 more Smart Citation
“…[431][432][433] More generally, they can neutralize strong acids in outdoor air. For example, Shen et al 434 found that amines, emitted during the burning of coal in the Yangtze River Delta region of China, react with nitric and sulfuric acids to form aminium salts (the salt that results from an amine reacting with a strong acid). Aminium nitrates were more abundant than aminium sulfates, with average concentrations of methylaminium, dimethylaminium, and ethylaminium salts in aerosol particles of 6 ± 3 ng/m 3 , 8 ± 5 ng/m 3 , and 20± 17 ng/m 3 , respectively.…”
Section: Acid-base Chemistry Of Amines and Amino Acidsmentioning
confidence: 99%
“…The mass concentrations and temporal distributions of amines in Chinese megacities (e.g., Guangzhou, Nanjing and Shanghai) have been studied extensively based on the traditional filter sampling methods ( Cheng et al, 2020 ; Liu et al, 2018 ; Shen et al, 2017 ). However, the traditional off-line sampling is time consuming and the samples may be reacted with each other during the sampling process.…”
Section: Introductionmentioning
confidence: 99%